Swelling properties of acrylamide-N,N’-methylene bis(acrylamide) hydrogels synthesized by using meso-2,3-dimercaptosuccinic acid-cerium(IV) redox couple (eXPRESS Polymer Letters)
In this paper, meso-2,3-dimercaptosuccinic acid-Ce(IV) redox couple is used for crosslinking polymerization of acrylamide (AAm) with N,N′-methylene bis(acrylamide) (MBAA) in acid aqueous medium. We have investigated the effects of crosslinker ratio, acid concentration and the molar ratio of AAm/Ce(IV) on the swelling behaviors of the synthesized P(AAm-MBAA) hydrogels. The experimental results show that the increase in the nAAm/nMBAA and nAAm/nCe(IV) result in an increase in the swelling ratio and rate of resulting hydrogels. However, the swelling equilibrium ratio and rate have been decreased with increasing of acid concentration. The k and n values in the equation of swelling rate have been determined. The n exponent decreases with increasing crosslinker, initiator and acid concentrations whereas k values increase. Kinetics and equilibrium swelling values have been discussed in terms of reaction parameters.